Analysis Of The Impact Of Chatgpt Use On Arabic Text Translation Skills: A Case Study Of Arabic Language Education Students Of The State Islamic University Of North Sumatra - Huwaina Rabithah Nur; Kiki Haura Shandi; Fadhla Abi Hidayah; Sahkholid Nasution (Jurnal Multidisiplin Sahombu, 2024)
The problem underlying this article's research is that many PBA 2 students, batch 21 UINSU, use ChatGPT in translating but there is no re-analysis of the results provided. This can be seen from the inability of students to be responsible for their translation results. The purpose of this study is to see what impacts are felt by PBA 2 students, batch 2021, due to the use of chatGPT on their translation skills . This study was conducted using qualitative methods. Data were collected through observation, interviews, and also the distribution of short essays via Google form . The collected data was then analyzed by grouping each answer based on the similarity of the answer pattern. The results of this study indicate that the use of chatGPT has 2 positive impacts and 5 negative impacts due to the positive impact on students' translation skills is that students are able to translate Arabic texts quickly and can practice producing neater word arrangements when translating. As a result of the 5 negative impacts, students do not master the basic skills for translating Arabic texts, which makes it difficult for them to produce perfect translations. 8 students ignore the truth of chatGPT, this is done based on 2 factors, namely the strategy of using chatGPT and also learning motivation .